The universal content of courtly virtues as a prerequisite for Renaissance humanism - Yefimenko, Vitaliy (Ukrainian Cultural Studies, 2022)
The article examines the formation of the foundations of the humanist ideology of the Renaissance in the culture of the European Middle Ages. The main stages of the formation and development of the culture of the Middle Ages and their achievements are traced. We pay attention on the "The Autumn of the Middle Ages" (J. Huizinga) and on such an important component of the culture of that time as the court culture, the culture of castles. It was during this period of a long era that the most important changes took place in the social and spiritual worlds of Europeans, which ultimately enabled the formation of the ideology of humanism with the system-forming worldview principle of anthropocentrism. On the examples of the work of troubadours and trouvers, Ch. de Troyes, B. de Born, the so-called of "marginal" sources that are, as it were, on the periphery of the text of medieval culture, but significantly supplement it ("The Miracles of Notre Dame" by Gautier de Coinci), an analysis is given of the filling of traditional courtly virtues with a new universal meaning, the affirmation of the worldview principle of anthropocentrism in the practice of human relations. The impact on this process of the Albigensian Crusade, a kind of catalyst for the growth of the demand for humanity in a society full of suffering and death, is noted. To virtues with a traditional meaning, such as kindness, generosity, courage, virtues with a humanistic meaning are added – mercy, love and friendship with vassals, care for subjects, equality with them in everything. New dramatic and even tragic dimensions of courtly virtues discovered by the troubadours during and after the Albigensians crusade became synonymous with humanism, a prerequisite for the formulation of the humanistic ideology of the Renaissance. The obvious connection with innovations in the system of the European society moral values, in the interpretation of the concept of common law, recognition of the right to autonomy in the development of a secular state is indicated.